The Relationship between Security and Customer Satisfaction in Digital Wallet Services - Amin, Nurelyana; Salim, Siti Aisyah (Research in Management of Technology and Business, 2025)
Digital wallets have become an essential part of how we make payments today, proving themselves to be one of the most important technologies of the 21st century. In Malaysia, increasing internet penetration and the growing number of smartphone users have driven widespread adoption of digital wallets for transactions. However, as smart technology continues to evolve rapidly, user concerns over security risks have intensified. Safeguarding personal information is critical in the digital landscape, and the security measures implemented by third-party online payment providers play a significant role in shaping customer satisfaction. This research aims to evaluate the key dimensions of digital wallet security that are highly valued by users in Malaysia, assess the level of customer satisfaction, and examine the relationship between these factors within the context of digital wallet services in Malaysia. The study focuses on the population of 1.2 million Malaysian university students who have used digital wallet services. Based on the Krejcie and Morgan table, the appropriate sample size for this study is 384 respondents. A quantitative research approach was adopted, utilizing a Google Form questionnaire to collect data. A total of 263 responses were gathered from university students in Malaysia, yielding a response rate of 68.49%. The collected data was analysed using the Statistical Package for Social Sciences (SPSS), producing quantitative reports in the form of frequency, percentage, mean, and standard deviation. The findings confirmed that all hypotheses were accepted, indicating significant relationships between all variables and customer satisfaction. Notably, the authentication dimension exhibited the highest correlation coefficient at 0.775, underscoring its strong influence on customer satisfaction.